The Geosciences: Selected Web Resources - Linda Zellmer (Issues in Science and Technology Librarianship)
Geological science, or more commonly geoscience, is a term that refers to the collection of scientific disciplines that study the Earth, including geology, paleontology, mineralogy, hydrology, and environmental geology, to name a few. This bibliography contains links to and brief descriptions of a variety of web resources, including reference works, publication indexes, style and citation manuals, photographs and images, earth science education resources as well as sources related to specific sub-disciplines of the geological sciences. It includes resources that can be used to teach and learn about the geosciences, as well as resources that might be useful to a wide variety of users, including students, researchers and the general public. Reprinted by permission of the publisher.